Full-mouth ultrasonic debridement in the treatment of patients with diabetes and severe chronic periodontitis: preliminary study - Ana Luísa Teixeira MEIRA; Camila NOBRE; Maísa CARDOZO NASCIMENTO; Marcelo NAPIMOGA; Renato CASARIN; Sandro BITTENCOURT; Érica DEL PELOSO RIBEIRO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: The purpose of this study was to clinically evaluate the effect of one-stage full-mouth ultrasonic debridement in the treatment of diabetic subjects with severe chronic periodontitis. Methods: Sixteen patients with uncontrolled diabetes (glycated hemoglobin ≥ 7%) and severe chronic periodontitis (at least 8 teeth with a probing depth and bleeding on probing were selected and randomly assigned to 2 treatment groups: control group (n=7) - quadrant-wise scaling and root planning; test group (n=9) - full-mouth ultrasonic debridement in one session of 45 minutes. The following outcomes were assessed: plaque index, gingival index, bleeding on probing, probing depth, clinical attachment level and gingival margin position. All parameters were assessed at baseline, 1 and 3 months after treatment. Probing depth, clinical attachment level and gingival margin position were analyzed using ANOVA and Tukey test, and the other clinical parameters analysed with the Friedman and Mann-Whitney tests. Results: An improvement in probing depth, clinical attachment level was observed after treatment in both groups, but without statistically significant differences between them. After 3 months, in initially deep pockets, the PD decreased 1.6 mm and 1.7 mm in test and control group, respectively. Clinical attachment level gain ≥ 2 mm was statistically significant at sites in control (10.1%) and test (13,4%) groups in 3 months. Conclusions: One-stage full-mouth ultrasonic debridement promoted similar clinical outcomes to those obtained with the scaling and root planning in the treatment of diabetic subjects with severe chronic periodontitis.